2000
DOI: 10.1152/jn.2000.84.5.2529
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Properties of Fast and Slow Neurons in the Pretectal Nucleus Lentiformis Mesencephali in Pigeons

Abstract: Neurons in the pretectal nucleus lentiformis mesencephali (LM) are involved in the analysis of optic flow that results from self-motion. Previous studies have shown that LM neurons have large receptive fields in the contralateral eye, are excited in response to largefield stimuli moving in a particular (preferred) direction, and are inhibited in response to motion in the opposite (anti-preferred) direction. We investigated the responses of LM neurons to sine wave gratings of varying spatial and temporal freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 37 publications
4
89
0
Order By: Relevance
“…In pigeons, nBOR cells are tuned by the spatio-temporal frequency (TF/SF) rather than by their angular velocity of stimuli (WolfOberhollenzer andKirschfeld, 1990, 1994). Similar experiments using a broader range of spatial frequencies have been carried out in the nBOR, the nLM (nucleus lentiformis mesencephali) and the vestibulo-cerebellum of pigeons (Wylie and Crowder, 2000;Crowder et al, 2003a;Winship et al, 2005). These experiments led to the definition of two types of cells found in the three structures: the 'slow neurones', which are most activated by gratings of high SFs (0.35-2.0·cycles·deg. )…”
Section: Structures and Mechanisms Underlying Context-dependantmentioning
confidence: 69%
“…In pigeons, nBOR cells are tuned by the spatio-temporal frequency (TF/SF) rather than by their angular velocity of stimuli (WolfOberhollenzer andKirschfeld, 1990, 1994). Similar experiments using a broader range of spatial frequencies have been carried out in the nBOR, the nLM (nucleus lentiformis mesencephali) and the vestibulo-cerebellum of pigeons (Wylie and Crowder, 2000;Crowder et al, 2003a;Winship et al, 2005). These experiments led to the definition of two types of cells found in the three structures: the 'slow neurones', which are most activated by gratings of high SFs (0.35-2.0·cycles·deg. )…”
Section: Structures and Mechanisms Underlying Context-dependantmentioning
confidence: 69%
“…An example of variable sensory integration comes from restrained pigeons that exhibit different head stabilization reflexes and tail responses to visual and vestibular perturbations during simulated flight than during resting conditions (16,17). At the level of sensory neurons, cells of the avian accessory optic system are divided into populations that differ in maximum sensitivity to either fast or slow motion (14,18,19). The functional roles and the relative abundance and distribution of fast and slow cells have not been described in any bird.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transient/sustained ratios at the onset of motion in the preferred direction were larger in the accelerationsensitive neurons, and the value of the transient/sustained ratio was related to the amount of acceleration responsiveness, indicating that part of the transient is related to the presence of response to stimulus acceleration. Previous studies have shown that many directional cells produce transient responses to the onset of motion (Ibbotson et al, 1998;Lisberger and Movshon, 1999;Wylie and Crowder, 2000;Priebe and Lisberger, 2002) and to the appearance of a stationary pattern (Müller et al, 2001;Gu et al, 2002). The onset transients in these cases could convey information about stimulus motion or edge detection (Awatramani and Slaughter, 2000) and may originate from the retinal bipolar cells and/or some synaptic mechanisms (Awatramani and Slaughter, 2000;Müller et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We have added an additional parallel between the vestibular and visual neurons in the optokinetic system. They are both sensitive to acceleration, although their physiological modalities (mechanical vs. visual) are quite different (Klinke, 1978;Fu et al, 1998a,b;Wylie and Crowder, 2000;Ibbotson and Price, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation